2011
DOI: 10.3109/1354750x.2011.613123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the course of biomarker changes and kidney injury in a rat model of drug-induced acute kidney injury

Abstract: These data suggested that establishment of a suitable biomarker panel would facilitate detection of site-specific kidney injury with high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…In fact, doxorubicin 3D tissues had a greater increase in NGAL secretion over time than did the same treatment groups in 2D. Sasaki et al has shown that rats dosed with cisplatin or gentamicin can take up to 7 days to have increased expression of Kim-1 and NGAL in their urine at high doses [38], indicating that our time course may be relevant to in vivo situations. Our data also shows the usefulness of our 3D model over 2D culture for the interpretation of biomarker data as the 3D tissues do not have as high a level of background expression as the 2D cultures.…”
Section: Resultsmentioning
confidence: 66%
“…In fact, doxorubicin 3D tissues had a greater increase in NGAL secretion over time than did the same treatment groups in 2D. Sasaki et al has shown that rats dosed with cisplatin or gentamicin can take up to 7 days to have increased expression of Kim-1 and NGAL in their urine at high doses [38], indicating that our time course may be relevant to in vivo situations. Our data also shows the usefulness of our 3D model over 2D culture for the interpretation of biomarker data as the 3D tissues do not have as high a level of background expression as the 2D cultures.…”
Section: Resultsmentioning
confidence: 66%
“…In 300,000 IU/kg/day of colistin dose received by second group, we found a significant uNGAL increase, suggesting that this parameter is more sensitive than pCysC for the detection of renal damage induced by treatment with colistin. Several studies either experimental in rats 22,23 or clinical in patients with different pathologies 24,25 revealed the importance of early detection of kidney lesions induced by drug or other nephrotoxic factors. Urine NGAL has also been shown to predict the severity of AKI and over-expressed in response to injury.…”
Section: Discussionmentioning
confidence: 99%
“…There currently are no biomarkers that can accurately track, correlate, or predict the occurrence of renal injury, particularly when related to drug-related toxicity [13]. There is a growing interest in the role of micro Ribonucleic Acids (miRNAs) in the pathogenesis of renal diseases [4, 5] and a growing number of investigations are directed to characterizing their potential as biomarkers [69].…”
Section: Introductionmentioning
confidence: 99%